The Emerging Role of Heat Shock Proteins in Nasopharyngeal Carcinoma: A Review - Ghavidel, Farideh; Moalefshahri, Razieh; Javid, Hossein; Rezagholinejad, Nastaran; Hashemy, Seyed Isaac (Current Medicinal Chemistry, 2025)
Several investigations have revealed that nasopharyngeal carcinoma (NPC), earlier known as lymphoepithelioma, originates from the nasopharynx epithelium (NPE). The global NPC incidence and mortality distribution reports have reported very high rates (more than 20-30 men per 100,000 men and 10 women per 100,000). Genetic background susceptibilities, Epstein-Barr virus (EBV), and their complex interaction are expressed as the pathophysiology. Also, radiotherapy of locoregional lesions is the main treatment for NPC because of the extremely radiosensitive feature of the non-keratinizing variety. On the other hand, surgical intervention might be used for recurrent situations, while simultaneous radiation and chemotherapy for advanced stages are preferable. Since specific disease symptoms do not appear early, biomarkers should be identified to facilitate diagnosis. As overexpression of heat shock proteins (HSPs) has been observed in various cancers, they can be a promising candidate biomarker for many malignancies. The purpose of this study was to peruse different pathogenic roles of a panel of HSPs, including their diagnostic, preventive, and remedial role in NPC, which may provide the basis for future discoveries of novel HSP-based biomarkers of NPC.
Keywords: NPC